Erythropoiesis‐driven regulation of hepcidin in human red cell disorders is better reflected through concentrations of soluble transferrin receptor rather than growth differentiation factor 15. Issue 4 (3rd March 2014) - Fertrin, Kleber Yotsumoto; Lanaro, Carolina; Franco‐Penteado, Carla Fernanda; de, Dulcinéia Martins; de, Mariana Rezende Bandeira; Pallis, Flávia Rubia; Bezerra, Marcos André Cavalcanti; Hatzlhofer, Betania Lucena Domingues; Olbina, Gordana; Olalla Saad, Sara Terezinha; da, Aderson; Westerman, Mark; et al.
<x xml:space="preserve">Abstract</x> Growth differentiation factor 15 (GDF‐15) is a bone marrow‐derived cytokine whose ability to suppress iron regulator hepcidin in vitro and increased concentrations found in patients with ineffective erythropoiesis (IE) suggest that hepcidin deficiency mediated by GDF‐15 may be the pathophysiological explanation for nontransfusional iron overload. We aimed to compare GDF‐15 production in anemic states with different types of erythropoietic dysfunction. Complete blood counts, biochemical markers of iron status, plasma hepcidin, GDF‐15, and known hepcidin regulators [interleukin‐6 and erythropoietin (EPO)] were measured in 87 patients with red cell disorders comprising IE and hemolytic states: thalassemia, sickle cell anemia, and cobalamin deficiency. Healthy volunteers were also evaluated for comparison. Neither overall increased EPO, nor variable GDF‐15 concentrations correlated with circulating hepcidin concentrations (P = 0.265 and P = 0.872). Relative hepcidin deficiency was found in disorders presenting with concurrent elevation of GDF‐15 and soluble transferrin receptor (sTfR), a biomarker of erythropoiesis, and sTfR had the strongest correlation with hepcidin (rS = −0.584, P < 0.0001). Our data show that high concentrations of GDF‐15 in vivo are not necessarily associated with pathological hepcidin reduction, and hepcidin deficiency was only found when associated with sTfR overproduction. sTfR elevation may be a necessary common denominator of erythropoiesis‐driven mechanisms to favor iron absorption in anemic states and appears a suitable target for investigative approaches to iron disorders. Am. J. Hematol. 89:385–390, 2014. © 2013 Wiley Periodicals, Inc.